Beyond one work day? A daily diary study on causal and reverse effects between experienced workplace incivility and behaving rude towards others. Issue 2 (4th March 2019) - Vahle-Hinz, Tim; Baethge, Anja; Van Dick, Rolf
ABSTRACT: In this diary study with N  = 348 employees, we examine whether the contagion effect of workplace incivility transfers beyond one work day that is whether the experience of workplace incivility is related to showing rude behaviours towards others the next day. Additionally, we examine whether ruminating in the evening of a work day and building an intention for revenge behaviour mediate this relationship, and explore whether a serial mediation process exists where experienced incivility triggers ruminative thoughts, which, in turn, increase the likelihood of intending to act, which transfers into actual rude behaviour the next day. Using a multilevel path analysis, our results confirmed a lagged relationship between workplace incivility one day and rude behaviours towards others the next day. Between-persons' workplace incivility was also related to showing rude behaviour towards others. Neither rumination nor revenge behaviour intent proved to be mediators of this relationship. Additionally, the serial mediation process was not confirmed; however, parts of the process—namely the relationship between experienced workplace incivility and ruminating about work in the evening—received support. Importantly, the reverse relationship (i.e., showing rude behaviour one day leads to experiencing workplace incivility the next) was not supported in our analysis. By adding a new, daily time perspective, our study suggests that participants do not intentionally provoke episodes of incivility, but rather react to others' incivility.